Analisis Faktor-faktor yang Mempengaruhi Relasi Kuasa Pelaku Kekerasan dalam Rumah Tangga (KDRT) - Melsi Syawitri; Afdal Afdal (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
Cases of violence in Indonesia, especially against women in the household, have increased so that it is considered quite alarming. Domestic violence perpetrated by the perpetrator, in this case the husband, is motivated by power relations in the household. This research aims to analyze the factors that influence the power relations of domestic violence (KDRT).The method used in this research is a descriptive qualitative approach with the research subject, namely a criminal case of domestic violence. The data collection techniques used were observation, interviews and document analysis. The data analysis technique is carried out through three activities, including data reduction, data presentation, and drawing conclusions.The result of the research shows that there is a real power relation of violence in household; (1) gender perception bias, based on the results found that there is an understanding that is still gender biased in the perceptions of domestic violence perpetrators, (2) aggressive personality is higher in men. This is related to the social roles inherent in men and women. So that with a reasonable view that aggressive is higher in men, causing the perpetrator to feel for verbal and physical aggression. The perpetrator who has an aggressive personality causes him to become irritable by participating in verbal and physical aggression. (3) The perpetrator who has an antisocial personality is related to the tendency to carry out criminal activities such as domestic violence without being followed by feelings related to the act of action. The results of the research are expected to help community institutions to pay more attention to the conditions of domestic violence perpetrators and especially counselors to be able to provide interventions in the form of counseling programs to perpetrators as preventive and handling measures in order to break the chain of domestic violence. It is also hoped that the counselor can educate the perpetrators to change their mindset and behavior and help them in the future to be able to integrate with society.